Osteopontin - The stirring multifunctional regulatory factor in multisystem aging - Du, Yuxiang; Mao, Liwei; Wang, Zhikun; Yan, Kai; Zhang, Lingli; Zou, Jun (Frontiers in Endocrinology, 2022)
Osteopontin (OPN) is a multifunctional noncollagenous matrix phosphoprotein that is expressed both intracellularly and extracellularly in a variety of tissues. As a growth regulatory protein and proinflammatory immunochemokine, OPN is involved in the pathological processes of many diseases. Recent studies have found that OPN is widely involved in the aging processes of multiple organ tissues, such as T-cell senescence, atherosclerosis, skeletal muscle regeneration, osteoporosis, neurodegenerative changes, hematopoietic stem cell reconstruction, and retinal aging. However, the regulatory role and mechanism of OPN in the aging process of different tissues are not uniform, and even the role of OPN in different developmental stages of the same tissue is diverse, which generates uncertainty for the future study and utilization of OPN. In this review, we will summarize the regulatory role and molecular mechanism of OPN in different tissues and cells, such as the musculoskeletal system, central nervous system, cardiovascular system, liver, and eye, during senescence. We believe that a further understanding of the mechanism of OPN in the aging process will help us to develop targeted and comprehensive therapeutic strategies to fight the spread of age-related diseases.